Re-Evaluating the Political Press: A Case Study on Political, Economic and Journalistic Functioning of the Inter-War Czechoslovak Party-press Newspaper Národní listy, and its Publishing Company the Prague Stock Printery (PAT) - Kubíčková,Vlaďka (2016)
This article attempts to re-assess the often negative evaluations of the political press, through a detailed analysis of a case study from inter-war Czechoslovakia, the newspaper Národní listy, and its publishing company the Prague Stock Printery (PAT), which were affiliated to the National Democratic Party. The analysis is theoretically framed by a discussion of notions of party-press parallelism and political parallelism, and how these political models are evaluated within the contemporary literature. In the following parts, an extensive (but necessary) contextualization is offered, which first focuses on the political-economic history of inter-war Czechoslovakia, and a description of its media landscape, and then details the workings of PAT and Národní listy. The analytical parts first describe the financial, managerial and editorial situation of PAT and Národní listy, and then evaluates their functioning at the economic, political and journalistic level. This evaluation shows the complexities of the political model from within the actual publishing practice, and demonstrates both the advantages and problems of the political model, compensating for the frequent exclusively negative evaluations of this model.